Planning the Reliable and Valid Assessment's Instrument for Business Model Canvas Comprehension - Wangi, Nisaul Barokati Seliro; Hariyadi, Ahmad; Kusniarti, Tuti; Firdaus, Winci; hudaa, Syihaabul (International Journal of Psychosocial Rehabilitation, 2020)
Business Model Canvas (BMC) is a Business Model nowadays it is considered important to be mastered by students in entrepreneurship courses as a starting point to plunge into the world of entrepreneurship because in BMC a framework is explained in a simple way to present the elements contained in a business model. Although considered important, it is very difficult to find an assessment instrument for this aspect. Even if there is, it is not a valid and reliable instrument. This article discusses the design of assessment instruments for BMCs at the College Level. There are 9 aspects of assessment used by the author according to Alexander Osterwalder in his book entitled Bussiness Model Generation which consists of 9 blocks of activity areas to map strategies to build strong businesses, consisting of Customers Segment, Value proposition, Customer Relationship, Channel, Revenue Stream, Key Resource, Key Activities, Key Partnership, and Cost Structure. To produce a quality assessment instrument, the authors tested the validity and reliability of the instrument. The current study authors involve expert entrepreneurship to examine the structure and substance of the assessment, also, the authors tested the instrument as a statistical test. This instrument is used to assess students' understanding of concepts in BMC. Based on the validity of experts Entrepreneurship and statistical analysis shows that aspects of assessment are appropriate to be used to test the ability to understand BMC concepts.